2010
DOI: 10.4103/0975-9476.72619
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis

Abstract: Ankylosing spondylitis belongs to a group of rheumatic diseases known as the spondyloarthropathies (SpA), which show a strong association with the genetic marker HLA-B27. Inflammatory back pain and stiffness are prominent early in the disease, whereas chronic, aggressive disease may produce pain and marked axial immobility or deformity. Modern medicine has no established treatment for it. From the Ayurvedic perspective, the disease can fall under amavata, which may be effectively managed when intervention is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“… 1 Previous studies indicated a strong correlation of AS and genetic marker HLA-B27. 2 Rather than functional impairment, there is involvement of entheses, peripheral joints and extra-articular organs, reduction of health-related quality of life (HRQoL). 3 Stiffness, pain, progressive loss of spine mobility may be key contributors to physical limitations for AS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Previous studies indicated a strong correlation of AS and genetic marker HLA-B27. 2 Rather than functional impairment, there is involvement of entheses, peripheral joints and extra-articular organs, reduction of health-related quality of life (HRQoL). 3 Stiffness, pain, progressive loss of spine mobility may be key contributors to physical limitations for AS patients.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Exercises seem to play an important role in management AS patients, particularly when performed in an outpatient group supervised by a physiotherapist or intensively in inpatients who showed a short-term improvement. 15 , 16 Nowadays, all kinds of forms of exercises such as educational sessions, supervised exercise, home-based exercise, spa, swimming, the Global Posture Reeducation method, Tai Chi, McKenzie, Heckscher, and Pilates methods, 17 yoga 2 and so on had been embedded in rehabilitation program for AS patients. 11 Some studies evaluated the impact of exercises on AS patients who did not receive prescribed TNF inhibitors 17 19 and obtained consistent result that exercises improved the clinical outcomes of AS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Various panchakama procedures and internal Ayurvedic medicines have been proved beneficial in the management of AS [4]. Previously published case reports has correlated AS with 'Asthi-majja gata vata', 'Amavata' according to Ayurveda and managed AS successfully with various panchakarma procedures and internal Ayurvedic medicines [4,5]. Here we are reporting a case of AS with 'Beta thalassemia' diagnosed as 'Asthi-majja gata vata' according to Ayurveda.…”
Section: Non-steroidalmentioning
confidence: 95%
“…pondylitis belongs to a group of rheumatic diseases known as spondyloarthropathies (SpA) (1). It is believed that the primary mechanism of its occurrence is autoimmunity or autoinflammation (2); hat is, it is a chronic inflammatory autoimmune disease that primarily affects the axial spine, with the hallmark of sacroiliitis, involving the adjacent joints, tendons, and ligaments.…”
Section: Introductionmentioning
confidence: 99%